Analisis Representasi Gender pada Buku Paket Bahasa Inggris - Iriana, Ghani Juliyanto; Mobit, Mobit; Kamil, Acep Bahrum (Jurnal Ilmiah Wahana Pendidikan, 2024)
Gender biases and stereotypes are still prevalent in language textbooks, although a few studies have identified instances of positive representation. This study investigates gender representation in the 7th-grade of Indonesian EFL textbooks published by the Ministry of Education, Culture, Research and Technology (MONECRT), which recently published with the new guideline of Merdeka Curriculum. Focusing on the portrayal of gendered character activities and domestic roles, the study employs critical discourse analysis (CDA) to examine both visual and verbal representations. Guided by Fairclough's three-dimensional framework and Van Leeuwen's elements of social practice, the findings revealed that activities portrayal of female was stereotyped as passive, dependent, needing others and characterized more evaluative. Furthermore, male portrayed as hasty and having poor time management. In contrast, the domestic role of gender portrayed equal as both father and mother depicted with housework activities including cooking and cleaning. To sum up, the portrayals of gendered character activities often perpetuate entrenched stereotypes, while emerging discourse shows positive representations of domestic roles. This study underscores the significance of increased awareness among teachers and textbook developers regarding gender-related issues in English education.